The Effect Of Current Ratio, Debt To Equity Ratio And Inventory Turn Over On Return On Assets On Consumer Goods Companies - Helman Helman (Eduvest - Journal of Universal Studies, 2021)
Consumer Goods industry is a sector that is considered sufficient to encourage the economic growth which has contributed the growth of the country's economy. There are various ratios that can be used as a measuring tool in research. This study uses the theories Current Ratio, Debt To Equity Ratio, Inventory Turn Over and Return On Assets. The method used in this study is a quantitative, and the type of research is quantitative descriptive, and the nature of the research is explanatory. Data collection was performed by means of documentation. Data analysis method used is multiple linear regression analysis. Population were consumer goods companies listed in Indonesia Stock Exchange (BEI) in the period of 2015 to 2018 totaling 26 companies. The 104 samples of the study were drawn by purposive sampling technique. The research used a classic assumption test such as the test for normality, multicollinearity, autocorrelation and heteroscedasticity. The research model used is multiple linear regression. The study concludes that simultaneously Current Ratio, Debt To Equity Ratio and Inventory Turn have a significant effect on Return On Assets. Partially, Current Ratio (CR) and Debt To Equity Ratio (DER) do not have a significant effect on Return On Assets (ROA) while the Inventory Turn Over has a significant effect on Return On Assets (ROA) of consumer goods companies listed in the Indonesia Stock Exchange in the period of 2015 -2018.